Use of ?-Acceptors in Charge-Transfer Complexation of Some Cephalosporins: Chloranilic Acid as a Spectrophotometric Titrant in Non-Aqueous Media - SALEH AL-ATTAS, AMIRAH (Asian Journal of Chemistry, 2010)
A spectrophotometric titration method is described for the determination of some cephalosporins and their dosage forms using 0.005 M chloranilic acid solution in 1,4-dioxane as the titrant. The end-points is determined by measuring the change in absorbance of the sample at 488-528 nm. Quantitative recoveries with good reproducibility are reported for cephalexin, cefadroxile, cefaclor, cefuroxime, cefoxitin, ceftazidine and ceftriaxone eight dosage forms. The leastsquares method for the end point location in the spectrophotometric titration is also proposed.